2012
DOI: 10.1038/modpathol.2011.138
|View full text |Cite
|
Sign up to set email alerts
|

The extent of retraction clefts correlates with lymphatic vessel density and VEGF-C expression and predicts nodal metastasis and poor prognosis in early-stage breast carcinoma

Abstract: Although the earliest feature of disseminated disease in breast cancer is regional lymph node involvement, little is known about the mechanisms whereby cancer cells interact with lymphatic endothelial cells and enter the lymphatic system. We have previously reported that the extensive presence of retraction clefts in breast carcinomas highly significantly correlates with lymphatic tumor spread and predicts poor outcome, suggesting that retraction clefts are not just fixation artifacts, but real potential space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 34 publications
8
30
1
13
Order By: Relevance
“…The majority of previous studies have identified that VEGF expression is significantly increased in metastatic breast ductal carcinoma and is correlated with the poor clinical outcomes in patients with early-stage breast cancer (12,(17)(18)(19). Furthermore, VEGF may be an independent prognostic factor for the disease-free survival and OS of breast cancer patients (20). Thus, anti-VEGF therapy may have potential in the treatment of patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies have identified that VEGF expression is significantly increased in metastatic breast ductal carcinoma and is correlated with the poor clinical outcomes in patients with early-stage breast cancer (12,(17)(18)(19). Furthermore, VEGF may be an independent prognostic factor for the disease-free survival and OS of breast cancer patients (20). Thus, anti-VEGF therapy may have potential in the treatment of patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The basement membranes of new lymphatic vessels are incomplete, and the endothelial cells do not connect tightly. These factors allow tumor cells to easily invade new lymphatic vessels and metastasize to regional lymph nodes or distant organs (1518). In recent years more research oncologists are becoming interested in the mechanisms of tumor-induced lymphangiogenesis in various tumors (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is one of the most common types of cancer among women worldwide (21,22). Over 50% of early-stage breast cancer patients have local lymph node metastasis (18). Moreover, regional lymph node metastasis in breast cancer is also one of the main factors that leads to breast cancer metastasis and poor prognosis (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…25 Some studies have shown that a retraction artifact is correlated with lymphatic invasion and nodal metastasis and predicts a poorer outcome in early stage breast carcinoma. 26,27 The retraction artifact may be an early stage in the development of micropapillary architecture. These studies suggest that IDC with any well-defined micropapillary carcinoma component is diagnostic of IMPC.…”
Section: Microscopic Pathologymentioning
confidence: 99%